Power, speed and anthropometric measures of Portuguese elite junior volleyball players - Joao, P. V.; Sattler, T.; Pereira, A. (World Congress of Performance Analysis of Sport IX, 2012)
The purpose of this study was to describe the main power performance and anthropometric characteristics in different components in professional male volleyball players in order to determine if differences exist in these characteristics according to playing position. Fourteen subjects were assessed on anthropometric factors and conditional components of Explosive Strength of the Lower Limbs, as countermovement jumps without ball [CMJ; CMJ in spike (CMJS) and block (CMJB)] and simulation of real action during the volleyball game (CMJSb and CMJBb) using Ergojump. Speed was evaluated in 20m sprint, using photocells. The difference between performance levels and the specific positions has been analyzed through independent measures of ANOVA analysis, followed by Tukey Post Hoc of multiple comparisons. 14 athletes were divided in 5 groups [middle blocker (n=3; 17.6±1,1 yrs.; 194±0.06 cm; 83.6±5.5 kg and 2.02±0.02 arm span); Libero (n=2; 17.5±0.7 yrs.; 178±0.02 cm; 68±4.2 kg and 1.83±0 arm span); Setter (n=3; 18.3±1.15yrs.; 184±0.04 cm; 75.3±7.57 kg and 1.86±0.03 arm span); opposite player (n=3; 16±1 yrs.; 189±0.01 cm; 71.6±8.62 kg and 1.93±0.08 arm span) and Z4 (n=3; 17.3±1.52yrs.; 190±0.05 cm; 78.6±13.5 kg and 1.99±0.03 arm span). The results indicated that anthropometric measure showed significant differences in height value (p=0.036). No other significant differences (p<0.05) were found between among groups for power. However, libero players were the most explosive in CMJ. Setter players were explosive in almost jump tests (CMJB, CMJR, CMJRb and CMJBb) and sprint time than the others. The Z4, middle blocker, and opposite player positional groups had considerably poorer explosive performance and speed than the libero and setter. Anthropometric and explosive differences exist among playing positions in elite male volleyball players (Marques, et al., 2009; João, et al., 2010). These findings provide some data for elite male volleyball players competing in specific individual playing positions. Explosive tasks should be performed without ball but also it may be developed by a simulation of real actions during volleyball game.